2021
DOI: 10.7759/cureus.17622
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of FIB-4 and FIB-5 Scores as Compared to Fibroscan for Assessment of Liver Fibrosis in Patients With Non-Alcoholic Fatty Liver Disease

Abstract: IntroductionLimited access/exorbitant cost of fibroscan and the associated risks with biopsy to assess fibrosis in nonalcoholic fatty liver disease (NAFLD) patients has made exigent demand of serum-based fibrosis scores to be validated for their accuracy and efficacy. The objective of the study was to compare the accuracy of FIB-4 (fibrosis-4) and FIB-5 (fibrofast) scores to rule out advanced fibrosis in NAFLD patients. MethodsA total of 145 patients were categorized as group I with mild/moderate fibrosis (MF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Also agree with previous studies [22] that found FIB-4 has great potential in diagnosing liver fibrosis caused by viral hepatitis and NAFLD in patients with advanced fibrosis . This was in agreement with Kumari et al [23], who concluded that FIB-4 is one of the best indices to assess liver fibrosis in NAFLD patients [23].…”
Section: Original Researchsupporting
confidence: 92%
See 1 more Smart Citation
“…Also agree with previous studies [22] that found FIB-4 has great potential in diagnosing liver fibrosis caused by viral hepatitis and NAFLD in patients with advanced fibrosis . This was in agreement with Kumari et al [23], who concluded that FIB-4 is one of the best indices to assess liver fibrosis in NAFLD patients [23].…”
Section: Original Researchsupporting
confidence: 92%
“…We also found in our study; that the FIB-5 score has no significant difference between groups. This was in agreement with Kolhe et al, who stated that FIB 5 could not be used to rule out advanced fibrosis [28], but this is in contrast to the previous study [23] that reported the FIB-5 score of the group with advanced fibrosis was significantly lower as compared with patients with mild to moderate fibrosis in NAFLD patients.…”
Section: Original Researchsupporting
confidence: 92%
“…Recent studies reported that a bro scan is the most accurate way to evaluate fatty liver, its grade, and brosis than liver biopsy as the gold standard (Foucher et al, 2006;Kumari et al, 2021). Other studies suggested that CAP is also preferred for the diagnosis of NAFLD (Group et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the brosis-4 (FIB-4) index was measured using the formula. FIB-4 index = [age × AST (units/l)] / (-platelet count (× 109/l) × [ALT (units/l)]1/2 (Kumari et al, 2021). The FIB-4 index was classi ed into three categories such as low risk: <1.3, intermediate risk: 1.3-2.67, and high risk: >2.67 (Kumari et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation